2017
DOI: 10.1016/j.cub.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Periodic Activation Patterns of Retrosplenial Cortex Encode Route Sub-spaces and Distance Traveled

Abstract: Traversal of a complicated route is often facilitated by considering it as a set of related sub-spaces. Such compartmentalization processes could occur within retrosplenial cortex, a structure whose neurons simultaneously encode position within routes and other spatial coordinate systems. Here, retrosplenial cortex neurons were recorded as rats traversed a track having recurrent structure at multiple scales. Consistent with a major role in compartmentalization of complex routes, individual retrosplenial cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
135
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 60 publications
16
135
0
Order By: Relevance
“…Future work should try to integrate the present account of spatial cognition with recent progress concerning spatial coding in parietal areas (Nitz, 2006; Nitz, 2009; Nitz, 2012; Harvey et al, 2012; Whitlock et al, 2012; Raposo et al, 2014; Vedder et al, 2017), and a broader view of retrosplenial function (e.g., Alexander and Nitz, 2015; Alexander and Nitz, 2017). Notably, BVCs were predicted by an early predecessor of the present model (Hartley et al, 2000; Burgess et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should try to integrate the present account of spatial cognition with recent progress concerning spatial coding in parietal areas (Nitz, 2006; Nitz, 2009; Nitz, 2012; Harvey et al, 2012; Whitlock et al, 2012; Raposo et al, 2014; Vedder et al, 2017), and a broader view of retrosplenial function (e.g., Alexander and Nitz, 2015; Alexander and Nitz, 2017). Notably, BVCs were predicted by an early predecessor of the present model (Hartley et al, 2000; Burgess et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a form of generalization termed pattern completion is commonly ascribed to be function of the highly recurrent neural network in CA3 (reviewed in Le Duigou, Simonnet, Telenczuk, Fricker, and Miles (); Knierim and Neunuebel ()); recent studies include Neunuebel and Knierim (); Lee et al (); Lu et al ()). Third, past work has shown that brain regions beyond the hippocampus encode similarities across spatial‐navigational experience (e.g., prefrontal [Jung, Qin, McNaughton, & Barnes, ], parietal [Nitz, ], retrosplenial [Alexander & Nitz, ; Alexander & Nitz, ], and entorhinal cortex [Frank et al, ; Derdikman et al, ]; discussion in [Grieves, Duvelle, Wood, & Dudchenko, ]). These brain regions can thus contribute spatially abstractive neural activity to target structures, among them the hippocampus.…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
“…In recent years there has been increased interest in characterizing the features of landmarks, in particular seeking to identify those traits that are helpful for building environmental representations and that facilitate effective wayfinding (Auger, Zeidman, & Maguire, 2017; Marchette, Vass, Ryan, & Epstein, 2015; Auger & Maguire, 2013; Auger, Mullally, & Maguire, 2012; Konkle & Oliva, 2012; Lew, 2011; Yoder, Clark, & Taube, 2011; Galati, Pelle, Berthoz, & Committeri, 2010; Committeri et al, 2004; Janzen & van Turennout, 2004). The brain areas that process these landmark features have also begun to be scrutinized with a view to understanding the neural evolution of environmental representations and the mechanisms involved (Alexander & Nitz, 2017; Auger et al, 2017; Chrastil, Sherrill, Aselcioglu, Hasselmo, & Stern, 2017; Mao, Kandler, McNaughton, & Bonin, 2017; Vedder, Miller, Harrison, & Smith, 2017; Shine, Valdés-Herrera, Hegarty, & Wolbers, 2016; Auger, Zeidman, & Maguire, 2015; Baumann & Mattingley, 2013; Aggleton, 2010; Iaria, Chen, Guariglia, Ptito, & Petrides, 2007; Wolbers, Weiller, & Büchel, 2004). …”
Section: Introductionmentioning
confidence: 99%